DYSTOCIA IN GOATS AND ITS MANAGEMENT - ODEDARA, MH; SUTHAR, BN; SUTARIA, TV; NAKHASHI, HC; SHARMA, VK (The Indian Journal of Animal Reproduction, 2016)
Out of goats suffering with maternal or fetal dystocia (n=6 each), the survival percent of dam was 91.7%. From 15 kids delivered, seven (46.7%) were live and eight (53.3%) were dead and twinning was observed in 25% goats.